Objective Methods of Muscle Tone Diagnosis and Their Application-A Critical Review - Kopecká, Barbora; Ravnik, David; Jelen, Karel; Bittner, Václav (Sensors, 2023)
"Muscle tone" is a clinically important and widely used term and palpation is a crucial skill for its diagnosis. However, the term is defined rather vaguely, and palpation is not measurable objectively. Therefore, several methods have been developed to measure muscle tone objectively, in terms of biomechanical properties of the muscle. This article aims to summarize these approaches. Through database searches, we identified those studies related to objective muscle tone measurement in vivo, in situ. Based on them, we described existing methods and devices and compared their reliability. Furthermore, we presented an extensive list of the use of these methods in different fields of research. Although it is believed by some authors that palpation cannot be replaced by a mechanical device, several methods have already proved their utility in muscle biomechanical property diagnosis. There appear to be two issues preventing wider usage of these objective methods in clinical practice. Firstly, a high variability of their reliability, and secondly, a lack of valid mathematical models that would provide the observed mechanical characteristics with a clear physical significance and allow the results to be compared with each other.
Keywords: Reproducibility of Results; Muscle Tonus; svalový tonus; Palpation; Muscles; reprodukovatelnost výsledků; svaly; Databases, Factual; databáze faktografické; palpace